I satelliti della missione EROS - De Corso, Stefano; Magrà¬, Daniele (GEOmedia, 2009)
EROS mission satellites The EROS (Earth Remote Observation Satellite) constellation is property of ImageSat International N.V. an international company and a commercial provider of high-resolution, satellite earth-imagery collected by its Earth Remote Observation Satellite. EROS A is equipped with a camera whose focal plane of CCD (Charge Coupled Device) detectors produces a standard image resolution of 1.9 meters. EROS B slightly larger and similar in appearance to EROS A, the new satellite has superior capabilities, including a larger camera of CCD/ TDI type (Charge Coupled Device/Time Delay Integration), with standard panchromatic resolution of 0.70 m at an altitude of about 500 km, a larger on-board recorder, improved pointing accuracy and a faster data communication link.